New 16th century Lithuanian compound names with stems of hypocoristic origin - Sinkevičiūtė, Daiva (Baltistica, 2022)
Compound names whose stems arose from hypocoristics constitute a subtype of Lithuanian names. Research of historical sources has revealed some new such names: Bučvilà, Bùgvydas (or Bgvydas), Bùtkvilas, Daũdvilas, Daũnepras, Daũtvilas, Eĩtgilas, Geĩtmantas, Kančeigãlas (or Kančeigáila), Nórgvilas, Tatavydas, Vaĩstvilas. It has also been shown that components originating in hypocoristics are found in the already known Daũdgėlas, Geĩtkantas, Geĩtvydas, Gibutkis. These names show that the inventory of proper names was expanded with parts of other names and that names originating in hypocoristics influenced compound names. The new stems buč-, bug- (or būg-), butk-, daud-, daut-, eit-, geit-, kanč-, nepr-, norg-, vaist- can be added to the already known buk-, darg-, eid-, eig-, jog-, jos-, tart-. The base of such stems originated in the first component of a compound name and the beginning of the second component, extended with a suffix. Except for darg- and vaist-, the stems are only found in Lithuanian names, which implies that they were created apart from Prussian.